ANALISIS FAKTOR PRODUKSI DAN KELAYAKAN USAHATANI CABE MERAH DI KELURAHAN SEI GOHONG KECAMATAN BUKIT BATU KOTA PALANGKA RAYA - Rajudinnor, Rajudinnor (J-SEA (JOURNAL SOCIO ECONOMIC AGRICULTURAL), 2018)
This study aimed to: i) analyze the influence of factors of production to the level of farm production Red Chillies, ii) determine the feasibility of farming Red Chillies during one production process, research was conducted in the village of Bukit Batu subdistrict Sei Gohong city of Palangkaraya. Total sample of farmers as many as 30 farmers was taken by simple random sampling (Sample Random Sampling) from the total population of Red Pepper farmers as many as 60 farmers. The analytical tool to answer the first objective equation is used Cobb Douglas: Y = boX1b1X2b2X3b3X4b4X5b5 where Y = production (kg), X1 = land area (Ha), X2 = Seed (kg), X3 = fertilizer (kg), X4 = pesticides (liter), X5 =labor (HOK), bo = coefficient parameter. While the analytical tool used to answer the second goal used analysis Revenue Cost Ratio (RCR), which is the ratio between the total revenue with the total cost of production. If RCR> 1 then farming is feasible to cultivate. The results showed that the factors of production land, seed, fertilizer, pesticides and labor simultan eously affect significantly against Red Chillies production in Sub Sei Gohong Bukit Batu subdistrict city of Palangka Raya. Value Fcount (97,513)> Ftable (2,409). Partially influence of each factor of production to production Red Chillies with a confidence level of 95%, the area of land with an elasticity of 0.329 (significant), seeds 0.150 (significant), fertilizer 0.314 (significant), pesticides 0.140 (significant), and labor -0.020 (not significant). The value of Revenue Cost Ratio of Red Chili farming is 3.2. It means that every production cost expense of Rp 1,000 will generate revenue of Rp 3,200, -. RCR> 1 means that Red Chilli farming in Kelurahan Sei Gohong District of Bukit Batu Kota Palangka Raya is feasible or profitable.